Revisiting the history of autism before Kanner and Asperger: a tribute to Grunya Sukhareva - Pozzi, Cristina Maria; Riesgo, Rudimar dos Santos; Assumpção Junior, Francisco Baptista (Arquivos de Neuro-Psiquiatria, 2024)
Almost two decades before Kanner's and Asperger's works, the original paper by child psychiatrist Grunya Efimovna Sukhareva had already been written. It was published in 1926 by Sukhareva in a German scientific journal of psychiatry and neurology, with a detailed description of children who presented clinical conditions whose characteristics and evolution closely resemble autism, according to current criteria. In the present historical note, we intend to present Sukhareva's pioneering work and retrieve the meaning of her original contribution.
Keywords: Autistic Disorder; Psychiatry; Asperger Syndrome